2010
DOI: 10.1093/brain/awq083
|View full text |Cite
|
Sign up to set email alerts
|

Human disease caused by loss of fast IIa myosin heavy chain due to recessive MYH2 mutations

Abstract: Striated muscle myosin heavy chain is a molecular motor protein that converts chemical energy into mechanical force. It is a major determinant of the physiological properties of each of the three muscle fibre types that make up the skeletal muscles. Heterozygous dominant missense mutations in myosin heavy chain genes cause various types of cardiomyopathy and skeletal myopathy, but the effects of myosin heavy chain null mutations in humans have not previously been reported. We have identified the first patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 21 publications
3
52
1
Order By: Relevance
“…8,10,18 A later study of patients of three unrelated families with a recessive myopathy, ophthalmoplegia and the absence of type 2A muscle fibers revealed that all patients were compound heterozygous for truncating mutations in MYH2. 11 More recently it was demonstrated that the affected individuals in a large family with recessive myopathy and ophthalmoplegia linked to chromosome 17 p13.1-p12 were homozygous for a frame shift mutation in MYH2 because of a single-base deletion. 20 In this study, MYH2 was considered as the plausible disease-causing gene because of the clinical findings of ophthalmoplegia in addition to muscle biopsy findings of absence or abnormal type 2A muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8,10,18 A later study of patients of three unrelated families with a recessive myopathy, ophthalmoplegia and the absence of type 2A muscle fibers revealed that all patients were compound heterozygous for truncating mutations in MYH2. 11 More recently it was demonstrated that the affected individuals in a large family with recessive myopathy and ophthalmoplegia linked to chromosome 17 p13.1-p12 were homozygous for a frame shift mutation in MYH2 because of a single-base deletion. 20 In this study, MYH2 was considered as the plausible disease-causing gene because of the clinical findings of ophthalmoplegia in addition to muscle biopsy findings of absence or abnormal type 2A muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The first primer pair spans exon 1 to 10 as previously described 11 and the second primer pair was 5 0 -GGAGGAAAAGTGA CGGTGAA-3 0 (forward primer, corresponding to nucleotide 169-188 of human MyHC IIa cDNA sequence; GenBank accession number: AF111784.1, GI: 4808812) combined with 5 0 -ATCTGTGGCCATCAGTTCTTCCT-3 0 (backward primer, corresponding to nucleotide 986-1008 of human MyHC IIa cDNA). The resulting PCR products were analyzed by sequencing.…”
Section: Dna Analysismentioning
confidence: 99%
See 3 more Smart Citations